2004
DOI: 10.1038/nature02484
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in cadherin 23 affect tip links in zebrafish sensory hair cells

Abstract: Hair cells have highly organized bundles of apical projections, or stereocilia, that are deflected by sound and movement. Displacement of stereocilia stretches linkages at the tips of stereocilia that are thought to gate mechanosensory channels. To identify the molecular machinery that mediates mechanotransduction in hair cells, zebrafish mutants were identified with defects in balance and hearing. In sputnik mutants, stereociliary bundles are splayed to various degrees, with individuals displaying reduced or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
254
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(271 citation statements)
references
References 29 publications
9
254
2
Order By: Relevance
“…The striking dichotomy that we observed in the lengths of tip links both in two-dimensional projection images and in three-dimensional tomographic reconstructions is also apparent in published images (Zhao et al 1996;Sollner et al 2004). Variations in tip-link dimensions cannot be attributed to tissue shrinkage, for in some instances long and short links coexisted in the same hair bundle.…”
Section: Organization Of Tip Linkssupporting
confidence: 66%
See 1 more Smart Citation
“…The striking dichotomy that we observed in the lengths of tip links both in two-dimensional projection images and in three-dimensional tomographic reconstructions is also apparent in published images (Zhao et al 1996;Sollner et al 2004). Variations in tip-link dimensions cannot be attributed to tissue shrinkage, for in some instances long and short links coexisted in the same hair bundle.…”
Section: Organization Of Tip Linkssupporting
confidence: 66%
“…The tip link may consist of glycosylated protein, for polycationic compounds label it (Neugebauer and Thurm 1987;Tsuprun and Santi 2000), and in avian preparations, it is severed by proteases only after deglycosylation (Kachar et al 2000). Genetic and immunological evidence localizes cadherin 23 to the tip link Sollner et al 2004), where it evidently constitutes the structure's upper two thirds (Kazmierczak et al 2007). The balance of the link is thought to consist of protocadherin 15 (Ahmed et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that null mutations in Cdh23 lead to profound deficits (v 2J , Table 2). Cdh23 has been reported to be a component of tip links in sensory hair cells Sollner et al, 2004); however, more recent reports suggest that Cdh23 is associated with transient lateral links in the developing hair bundles of cochlear sensory cells (Michel et al 2005;Lagziel et al 2005). Interestingly, +/lc is maintained on a C57 Â CBA background, and both of these strains (C57BL/6J and CBA/CaJ) have normal VsEPs up to at least 190 days old.…”
Section: Discussionmentioning
confidence: 97%
“…The protocadherin LKC is associated with contact inhibition of cell proliferation, and has been suggested as a candidate TSG for colon and liver cancer (Okazaki et al, 2002). Mutations in protocadherin 15 as well as CDH23 have also been implicated in Usher syndrome (Bolz et al, 2001;Di et al, 2001;Siemens et al, 2002), as recently demonstrated in a zebrafish model Sollner et al, 2004).…”
Section: Introductionmentioning
confidence: 95%